Public education for the children left behind - Carmen Camacho; I-ling Shen (Institute for the Study of Labor (IZA), 2010)
This paper examines the role of public education in the context of parental migration, and it studies the effects of an expansive income tax policy that is adopted to increase public education expenditure per pupil. It is shown that such a policy may exacerbate income inequality in the long run if for the less skilled dynasties, the benefits of more public spending on education does not make up for the negative effects of increased parental absences. However, if the migration-induced tax base erosion is not severe, an expansive income tax policy indeed enhances future human capital for all dynasties, and moreover, it may help the less skilled households escape from the poverty trap, thus reducing long-run income inequality.
Keywords: H20; H52; O15; O40; 330; Human capital; income inequality; parental migration; public education expenditure; tax base erosion; Öffentliche Bildungsausgaben; Bildungsinvestition; Eltern; Internationale Wanderung; Einkommensteuerpolitik; Steueraufkommen; Einkommensverteilung; Bildungsniveau; Theorie